Negative electrode active material

By adding two particles with a specific volume expansion rate to the negative electrode active material of the lithium-ion battery, the problems of electrode collapse and cycle characteristics are solved, and the high electrode capacity and good cycle characteristics are achieved.

CN119604989APending Publication Date: 2025-03-11DAIDO STEEL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380055924.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-17
Filing Date
2023-07-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

While improving the circulation characteristics and electrode capacity of the negative electrode active material of lithium-ion battery, it is difficult to take into account both, and the problem of electrode collapse still exists.

Method used

By adding two different particles with a volume expansion rate within a specific range to the negative electrode active material, including Si particles, the first particle (volume expansion rate 0 to 80%) and the second particle (volume expansion rate 100 to 300%), the stress caused by the expansion difference is relieved and the electrode collapse is suppressed.

Benefits of technology

It is achieved to significantly improve the circulation characteristics of lithium-ion batteries while maintaining high electrode capacity and extend the service life of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255244870000121
    Figure BDA0005255244870000121
  • Figure BDA0005255244870000131
    Figure BDA0005255244870000131
Patent Text Reader

Abstract

The present invention relates to a negative electrode active material containing Si particles, first particles, and second particles, the first particles having a volume expansion rate due to Li adsorption of 0-80%, and the second particles having a volume expansion rate due to Li adsorption of 100-300%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a negative electrode active material. Background Art

[0002] Lithium-ion batteries have the advantages of high capacity, high voltage and miniaturization, and are widely used as power sources for mobile phones and laptop computers, etc. In addition, in recent years, they have been highly anticipated as power sources for electric vehicles and hybrid vehicles, etc., and are being actively developed.

[0003] In a lithium-ion battery, charging and discharging are performed with the movement of lithium ions between the positive electrode and the negative electrode. On the negative electrode side, Li ions are absorbed into the negative electrode active material during charging, and Li ions are released from the negative electrode active material during discharging.

[0004] As the negative electrode active material used in the negative electrode, carbon materials such as graphite are widely used, but the theoretical capacity of graphite is only 372 mAh / g. Therefore, in order to increase the capacity, metal materials such as Si or Sn are explored as alternative materials to carbon-based negative electrode materials.

[0005] It is expected that Si and Sn will have high capacities of about 3600 mAh / g and 800 mAh / g, respectively. On the other hand, large volume changes such as expansion and contraction occur with the storage and release of lithium ions. Due to this volume change, the negative electrode active material is peeled off from the collector, causing the electrode to collapse and reducing the cycle characteristics.

[0006] On the other hand, a method of suppressing electrode collapse by mixing a material having a small volume expansion coefficient when occluding lithium ions (hereinafter, sometimes simply referred to as “Li occlusion”) is being studied.

[0007] For example, Patent Document 1 discloses a negative electrode active material for a lithium secondary battery, which has a Si alloy in which Si microcrystals are dispersed in a first metal matrix, and the Si alloy is dispersed in a second metal matrix having Li activity. By making this structure, the collapse of the Si alloy accompanying the absorption / release of lithium ions is suppressed, and since the negative electrode active material is difficult to fall off from the collector, the cycle characteristics can be improved.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: (Japanese) Patent Publication No. 2012-14866 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the effect of electrode collapse in the case of mixing materials with a small volume expansion rate is limited, and the effect of improving the cycle characteristics is limited. Thus, further improvement is expected for the deterioration of the cycle characteristics caused by the stress generated by the absorption / release of lithium ions. In addition, it is difficult to take into account both good cycle characteristics and the maintenance of high electrode capacity.

[0013] Therefore, an object of the present invention is to provide a negative electrode active material which maintains a high electrode capacity and has good cycle characteristics.

[0014] Technical solutions to solve problems

[0015] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by preparing a negative electrode active material containing two different particles having a volume expansion coefficient within a specific range in addition to Si particles, thereby completing the present invention.

[0016] That is, the present invention relates to the following [1] to [8].

[0017] [1] A negative electrode active material comprising Si particles, first particles and second particles,

[0018] The volume expansion rate of the first particle caused by Li absorption is 0 to 80%,

[0019] The volume expansion rate of the second particles due to Li absorption is 100 to 300%.

[0020] [2] The negative electrode active material according to [1], characterized in that

[0021] The average particle size of the Si particles and the average particle size of the second particles are both 5 μm or less.

[0022] [3] The negative electrode active material according to [1], characterized in that

[0023] The content of the Si particles is 20 to 80% by mass, the content of the first particles is 10 to 70% by mass, and the content of the second particles is 1 to 60% by mass.

[0024] [4] The negative electrode active material according to [3], characterized in that

[0025] The content of the first particles is greater than the content of the second particles.

[0026] [5] The negative electrode active material according to [1], characterized in that

[0027] The first particles are at least one particle selected from Fe, Al, Si and oxides thereof, and Ni, Ti, Cu, B, C, SiC and Si alloys.

[0028] [6] The negative electrode active material according to [1], characterized in that

[0029] The second particles are at least one particle selected from the group consisting of AlNi, AlTi, AlFe, and AlCu.

[0030] [7] The negative electrode active material according to [6], characterized in that

[0031] The second particles have an oxygen content of 4 mass % or less.

[0032] [8] The negative electrode active material according to any one of [1] to [7], characterized in that

[0033] The negative electrode active material is used in a lithium ion battery.

[0034] Effects of the Invention

[0035] According to the negative electrode active material of the present invention, it is possible to maintain a high electrode capacity while also achieving good cycle characteristics. Therefore, by applying the negative electrode active material to lithium ion batteries, it is expected that lithium ion batteries with small size and high energy density will be put into practical use. DETAILED DESCRIPTION

[0036] Below, the present invention is described in detail, but the present invention is not limited to the following embodiments, and can be arbitrarily deformed and implemented without departing from the scope of the gist of the present invention. In addition, the " to " representing the numerical range is used to include the numerical value recorded before and after it as the meaning of the lower limit and upper limit.

[0037] <Negative Electrode Active Material>

[0038] The negative electrode active material of the present embodiment includes Si particles, first particles, and second particles.

[0039] The volume expansion rate of the first particles due to Li absorption is 0 to 80%, and the volume expansion rate of the second particles due to Li absorption is 100 to 300%.

[0040] In addition, in this specification, the volume expansion rate due to Li absorption may be simply referred to as "volume expansion rate".

[0041] The theoretical capacity of Si particles is as high as 3600 mAh / g, but the volume expansion rate when absorbing lithium ions is 380%. Therefore, if Si particles are made to absorb / release lithium ions, good cycle characteristics cannot be obtained due to the rupture of Si particles or peeling from the collector caused by expansion / contraction stress.

[0042] In contrast, a method of adding particles whose volume change during charge and discharge is smaller than that of Si particles has been discussed. However, when Si particles absorb lithium ions and expand in volume, the expansion difference with the particles whose volume change is smaller is large, and a large stress is still generated in the negative electrode. As a result, the collapse of the electrode cannot be fully suppressed.

[0043] In contrast, it was found that the negative electrode active material of this embodiment can alleviate the stress caused by the expansion difference by containing Si particles and two different particles whose volume expansion coefficients due to Li absorption are within a specific range. As a result, the collapse of the electrode is suppressed and good cycle characteristics are achieved.

[0044] Specifically, the negative electrode active material of the present embodiment contains, in addition to Si particles, first particles having a volume expansion coefficient due to Li absorption of 0 to 80% and second particles having a volume expansion coefficient due to Li absorption of 100 to 300%.

[0045] It should be noted that in this specification, the volume expansion rate refers to the volume change rate before and after Li absorption when the target particles are subjected to Li absorption under the same conditions as the charging conditions in which the Si particles absorb lithium ions to the maximum and the volume expansion rate is 380%. Specifically, it refers to the increase in volume (volume %) after Li absorption based on the volume before Li absorption. That is, a volume expansion rate of 0% means that there is no volume change accompanying Li absorption, and a volume expansion rate of 100% means that the volume becomes twice the original volume before Li absorption accompanying Li absorption.

[0046] A working electrode using each particle was prepared, and the thickness of the electrode before and after charging, i.e., before and after Li absorption, was measured using a micrometer. The change in electrode thickness was converted into a change in volume, thereby determining the volume expansion rate. The working electrode manufacturing conditions and charging conditions are as follows.

[0047] Acetylene black (conductive aid) and polyimide (binder) were mixed in a ratio of 80:5:15 (mass ratio) with respect to particles with a particle size of about 15 μm to prepare a slurry. The slurry was applied to a stainless steel (SUS316L) foil with a thickness of 50 μm and dried to obtain a working electrode.

[0048] Next, a half-cell was prepared in which the counter electrode was a Li foil and a non-aqueous electrolyte was used. The non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1 mol / L in a mixed solvent of ethylene carbonate (EC) / dimethyl carbonate (DEC) = 1 / 1 (molar ratio).

[0049] The obtained half-cell was charged at a constant current of 0.1 mA until the voltage reached 0.002 Vvs. [Li + / Li]. The charging conditions are such that lithium ions are absorbed until the volume expansion rate of the Si particles reaches 380%.

[0050] The volume expansion rate of the first particles due to Li absorption is 0 to 80%. Since the negative electrode active material contains the first particles, even if the Si particles undergo large volume expansion / contraction accompanying Li absorption / release, the volume change of the entire electrode can be suppressed, thereby preventing the collapse of the electrode.

[0051] The volume expansion rate of the first particle is 0 to 80%, preferably 5 to 70%, more preferably 8 to 60%, and further preferably 10 to 55%. Here, from the perspective of easing the expansion difference with the Si particles and the second particles, the volume expansion rate of the first particle is 0% or more, preferably 5% or more, more preferably 8% or more, and further preferably 10% or more. In addition, from the perspective of suppressing the volume change of the entire electrode accompanying the absorption / release of Li, the volume expansion rate of the first particle is 80% or less, preferably 70% or less, more preferably 60% or less, and further preferably 55% or less.

[0052] The volume expansion rate of the second particles due to Li absorption is 100 to 300%. The negative electrode active material contains the second particles, which alleviates the stress caused by the difference in volume expansion rate between the Si particles and the first particles, and reduces the stress in the negative electrode active material, thereby preventing the collapse of the electrode.

[0053] The volume expansion coefficient of the second particle is 100 to 300%, preferably 140 to 280%, more preferably 170 to 265%, and further preferably 200 to 250%. Here, from the viewpoint of setting a more appropriate difference in volume expansion coefficient with the first particle and better relieving stress generation by approaching the volume expansion coefficient of the Si particle, the volume expansion coefficient of the second particle is 100% or more, preferably 140% or more, more preferably 170% or more, and further preferably 200% or more. In addition, from the viewpoint of setting a more appropriate difference in volume expansion coefficient with the Si particle and better relieving stress generation by approaching the volume expansion coefficient of the first particle, the volume expansion coefficient of the second particle is 300% or less, preferably 280% or less, more preferably 265% or less, and further preferably 250% or less.

[0054] When the absolute value of the difference between the volume expansion coefficient of the Si particle (380%) and the volume expansion coefficient of the second particle is set to ΔV1, and the absolute value of the difference between the volume expansion coefficient of the second particle and the volume expansion coefficient of the first particle is set to ΔV2, from the viewpoint of suppressing the collapse of the electrode and achieving good cycle characteristics, the ratio represented by ΔV1:ΔV2 is preferably 1:1 to 1:2, more preferably 1:1.2 to 1:2, further preferably 1:1.4 to 1:2, and further preferably 1:1.4 to 1:1.7.

[0055] The average particle size of the Si particles is not particularly limited, but is preferably 0.5 to 10 μm, more preferably 1 to 8 μm, and further preferably 1 to 5 μm. Here, from the viewpoint of suppressing the decomposition reaction of the electrolyte caused by the increase in the specific surface area of ​​the powder, the average particle size of the Si particles is preferably 0.5 μm or more, and more preferably 1 μm or more. In addition, since the smaller the average particle size, the smaller the absolute amount of volume expansion, from the viewpoint of achieving better cycle characteristics, the average particle size of the Si particles is preferably 10 μm or less, more preferably 8 μm or less, and further preferably 5 μm or less.

[0056] The average particle size of the Si particles can be adjusted by classifying the Si particles as needed using an appropriate pulverization method such as a ball mill, a disc mill, a coffee grinder, or a mortar grinder.

[0057] In addition, the average particle size in this specification refers to the median particle size (D50) calculated from the volume-based particle size distribution measured using a laser diffraction / scattering particle size distribution analyzer.

[0058] The average particle size of the second particles is not particularly limited, and is preferably 0.5 to 10 μm, more preferably 1 to 8 μm, and further preferably 1 to 5 μm. Here, from the viewpoint of suppressing the decomposition reaction of the electrolyte caused by the increase in the specific surface area of ​​the powder, the average particle size of the second particles is preferably 0.5 μm or more, and more preferably 1 μm or more. In addition, since the smaller the average particle size, the smaller the absolute amount of volume expansion, from the viewpoint of achieving better cycle characteristics, the average particle size of the second particles is preferably 10 μm or less, more preferably 8 μm or less, and further preferably 5 μm or less.

[0059] Similar to the average particle size of the Si particles, the average particle size of the second particles can be adjusted by pulverization or, if necessary, classification.

[0060] The average particle diameters of the Si particles and the second particles are both more preferably 0.5 μm or more, and both are more preferably 5 μm or less. The average particle diameters of the particles can be changed within the above-described ranges.

[0061] Since the first particles have a small volume expansion coefficient, the average particle size has a limited effect on the cycle characteristics compared to Si particles or second particles. Therefore, the average particle size of the first particles is not particularly limited, and may be, for example, 0.5 to 10 μm, 1 to 8 μm, or 1 to 5 μm. Here, the average particle size of the first particles may be, for example, greater than 0.5 μm, or greater than 1 μm, and may be, for example, less than 10 μm, less than 8 μm, or less than 5 μm.

[0062] Similar to the average particle size of the Si particles or the second particles, the average particle size of the first particles can also be adjusted by pulverizing or, if necessary, classifying.

[0063] The content of Si particles in the negative electrode active material is preferably 15 to 85% by mass, more preferably 20 to 80% by mass, further preferably 30 to 75% by mass, and particularly preferably 40 to 75% by mass. Here, from the viewpoint of obtaining a high electrode capacity, the content of Si particles is preferably 15% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, and particularly preferably 40% by mass or more. In addition, from the viewpoint of obtaining good cycle characteristics, the content of Si particles is preferably 85% by mass or less, more preferably 80% by mass or less, and further preferably 75% by mass or less.

[0064] The content of the first particles in the negative electrode active material is preferably 10 to 80% by mass, more preferably 10 to 70% by mass, and further preferably 20 to 60% by mass. Here, from the viewpoint of obtaining good cycle characteristics, the content of the first particles is preferably 10% by mass or more, and more preferably 20% by mass or more. In addition, from the viewpoint of obtaining a high electrode capacity, the content of the first particles is preferably 80% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less.

[0065] In addition, when two or more types of first particles are contained, the total content of them is preferably within the above range.

[0066] The content of the second particles in the negative electrode active material is preferably 1 to 60% by mass, more preferably 2 to 55% by mass, and further preferably 5 to 40% by mass. Here, from the viewpoint of obtaining good cycle characteristics, the content of the second particles is preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 5% by mass or more. In addition, from the viewpoint of obtaining a high electrode capacity, the content of the second particles is preferably 60% by mass or less, more preferably 55% by mass or less, and further preferably 40% by mass or less.

[0067] In addition, when two or more types of second particles are contained, the total content of them is preferably within the above range.

[0068] Based on the above, as a combination of the contents of the particles in the negative electrode active material of this embodiment, it is preferred that the content of the Si particles is 20 to 80% by mass, the content of the first particles is 10 to 70% by mass, and the content of the second particles is 1 to 60% by mass. The contents of the particles can be changed within the ranges described above.

[0069] When the negative electrode active material contains particles other than Si particles, first particles and second particles, the contents of the Si particles, first particles and second particles can be replaced by the content ratio of Si particles, first particles and second particles in mass % as a preferred aspect.

[0070] From the viewpoint of reducing the overall volume expansion rate of the negative electrode active material and obtaining good cycle characteristics, it is preferred that the content of the first particle is greater than the content of the second particle in the negative electrode active material. Specifically, the difference between the content of the first particle expressed in mass% and the content of the second particle is preferably 10% by mass or more and less than 80% by mass, and more preferably 20 to 60% by mass. Here, from the viewpoint of obtaining good cycle characteristics, the above difference is preferably 10% by mass or more, and more preferably 20% by mass or more. In addition, from the viewpoint of containing a certain amount of Si particles and maintaining the electrode capacity brought by the Si particles, the above difference is preferably less than 80% by mass, and more preferably less than 60% by mass.

[0071] The first particles are not particularly limited as long as the volume expansion coefficient due to Li absorption is 0 to 80%, and are preferably at least one particle selected from Fe, Al, Si and oxides thereof, and Ni, Ti, Cu, B, C, SiC and Si alloys.

[0072] Examples of oxides of Fe, Al, and Si include FeO, Fe2O3, Al2O3, and SiO2.

[0073] Examples of Si alloys include Si2Fe, Si2Ti, Si2Ni, Si2Zr, Si2Cr, Si2Co, and Si2Mn.

[0074] The second particles are not particularly limited as long as the volume expansion coefficient due to Li absorption is 100 to 300%, and are preferably at least one particle selected from the group consisting of AlNi, AlTi, AlFe, and AlCu.

[0075] It can be seen that the oxygen content of the second particle affects the volume expansion rate caused by Li absorption of the second particle. From the perspective of inferring the original volume expansion rate of the second particle, the oxygen content of the second particle is preferably 4% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less. The lower the oxygen content, the better, but it is usually 0.1% by mass or more.

[0076] In addition, in this specification, the oxygen content uses the value obtained by the heating melting infrared absorption method performed in an inert gas.

[0077] From the viewpoint of not hindering Li storage / release as an active material, the oxygen content of the Si particles is preferably 10 mass % or less, more preferably 5 mass % or less, and further preferably 1 mass % or less. The lower the oxygen content, the better, but it is usually 0.1 mass % or more.

[0078] The negative electrode active material of the present embodiment may contain other particles in addition to the Si particles, the first particles, and the second particles within a range that does not impair the effects of the present invention.

[0079] As for other particles, for example, particles having a volume expansion rate of more than 80% and less than 100% due to Li absorption can be cited. In addition, particles having a volume expansion rate of more than 300% may also be contained. However, relative to the volume expansion rate of 380% of Si particles, the first particles and the second particles are contained for the purpose of suppressing the expansion of the entire negative electrode active material or relieving stress, so there is no need to actively add particles having a volume expansion rate of more than 300% for the same purpose. By containing other particles, it is also preferred to contain the other particles when the effects unique to the other particles are exerted.

[0080] In the case of particles having a volume expansion rate of more than 80% and less than 100% or other particles that exert the above-mentioned unique effects, the total content of these particles is preferably 0 to 10% by mass, more preferably 1 to 8% by mass, and further preferably 2 to 7% by mass. Here, from the viewpoint of mitigation of the volume expansion difference or the viewpoint of suitably discovering the above-mentioned unique effects, the above-mentioned total content is preferably 0% by mass or more, more preferably 1% by mass or more, and further preferably 2% by mass or more. In addition, from the viewpoint of effectively exerting the effects of the first particles and the second particles relative to the Si particles, the above-mentioned total content is preferably 10% by mass or less, more preferably 8% by mass or less, and further preferably 7% by mass or less.

[0081] The method for producing the negative electrode active material of the present embodiment is not particularly limited.

[0082] Si particles, first particles, and second particles can be commercially available particles or synthesized particles. In the case of synthesis, they can be manufactured by a conventionally known method. In the case where the negative electrode active material contains other particles, the other particles can also be commercially available particles or synthesized particles.

[0083] Even if Si particles, first particles, second particles, and any other particles are mixed with particles of preferred average particle diameters, they may be pulverized or classified after mixing. The present invention is characterized in that they are preferably pulverized after mixing from the viewpoint of suppressing particle diameter variation.

[0084] The negative electrode active material of this embodiment is preferably used in a lithium ion battery.

[0085] When used in a lithium ion battery, the negative electrode active material of the present embodiment is provided on a conductive substrate together with a conductive auxiliary agent, a binder, etc. as necessary to constitute a negative electrode.

[0086] When the negative electrode active material of this embodiment is used in a lithium ion battery, the charging capacity per unit weight of the negative electrode active material is preferably 500 mAh / g or more, more preferably 1000 mAh / g or more, and further preferably 2500 mAh / g or more, based on the initial charging capacity of the first cycle. The higher the capacity, the better.

[0087] In addition, when 50 cycles of charge and discharge are carried out at a rate of 1 / 5C, i.e., charging or discharging within 5 hours, the capacity retention rate calculated by {discharge capacity after 50 cycles / initial discharge capacity (discharge capacity of the first cycle)}×100(%) is preferably 50% or more, more preferably 70% or more, and further preferably 90% or more, and the higher the better.

[0088] When the negative electrode is formed using a negative electrode active material, the conductive substrate functions as a current collector. The conductive substrate can be a material used as a current collector for the negative electrode in the past, for example, Cu, Ni, Fe or alloys thereof. It is characterized in that Cu or a Cu alloy is preferred.

[0089] The conductive substrate can be in a foil or plate shape, and is preferably in a foil shape from the viewpoint of miniaturization and freedom of shape.

[0090] Adhesives can use conventionally known adhesives, for example, fluororesins such as polyvinylidene fluoride (PVdF) resins and polytetrafluoroethylene, polyvinyl alcohol resins, polyimide resins, polyamide resins, polyamideimide resins, styrene butadiene (SBR), polyacrylic acid, etc. can be cited. They can be used alone or in combination of two or more. It is characterized in that, from the viewpoints of stability in electrochemical reactions or strength of adhesive force, polyimide resins are preferred.

[0091] The conductive aid can be any conventionally known conductive aid, for example, carbon black such as Ketjen black, acetylene black, furnace black, graphite, carbon nanotubes, fullerene, etc. These can be used alone or in combination of two or more. It is characterized in that, from the viewpoint of electronic conductivity, Ketjen black or acetylene black is preferred.

[0092] The negative electrode active material, the binder, and the conductive aid can be mixed in a conventionally known ratio to form the negative electrode. The film thickness of the negative electrode is also arbitrary.

[0093] When manufacturing the negative electrode, for example, the negative electrode active material, binder and conductive aid are dissolved or dispersed in a solvent to prepare a paste, and the paste is applied to the surface of the conductive substrate and dried, and optionally compacted or heat treated to obtain the negative electrode.

[0094] The negative electrode active material of the present embodiment has been described in detail above. However, another embodiment of the negative electrode active material of the present embodiment is as follows.

[0095] [1] A negative electrode active material comprising Si particles, first particles and second particles,

[0096] The volume expansion rate of the first particle caused by Li absorption is 0 to 80%.

[0097] The volume expansion rate of the second particles due to Li absorption is 100 to 300%.

[0098] [2] The negative electrode active material according to [1] above, characterized in that

[0099] The average particle size of the Si particles and the average particle size of the second particles are both 5 μm or less.

[0100] [3] The negative electrode active material according to [1] or [2] above, characterized in that

[0101] The content of the Si particles is 20 to 80% by mass, the content of the first particles is 10 to 70% by mass, and the content of the second particles is 1 to 60% by mass.

[0102] [4] The negative electrode active material according to [3] above, characterized in that

[0103] The content of the first particles is greater than the content of the second particles.

[0104] [5] The negative electrode active material according to any one of [1] to [4] above, characterized in that

[0105] The first particles are at least one particle selected from Fe, Al, Si and oxides thereof, and Ni, Ti, Cu, B, C, SiC and Si alloys.

[0106] [6] The negative electrode active material according to any one of [1] to [5] above, characterized in that

[0107] The second particles are at least one particle selected from the group consisting of AlNi, AlTi, AlFe, and AlCu.

[0108] [7] The negative electrode active material according to [6] above, characterized in that

[0109] The second particles have an oxygen content of 4 mass % or less.

[0110] [8] The negative electrode active material according to any one of [1] to [7] above, characterized in that

[0111] This negative electrode active material is used in lithium-ion batteries.

[0112] Example

[0113] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited thereto.

[0114] [Examples 1 to 30 and Comparative Examples 1 to 6]

[0115] Si particles and particles A and B listed in Table 1 were mixed under wet conditions using a bead mill. The mixing ratio of each particle, i.e., the content of each particle, is as shown in Table 1. It should be noted that "-" in Comparative Examples 4 and 5 means that particle B was not mixed, and only Si particles and particles A were mixed.

[0116] In addition, Si, Fe, and AlNi in each particle were produced by the following method.

[0117] Powdered Si particles are produced by spraying dissolved Si using a gas atomization method.

[0118] Fe and AlNi particles were also prepared into powdered particles by gas atomization. It should be noted that the oxygen content of the AlNi particles used in Comparative Example 6 was adjusted by immersing the particles in water.

[0119] Each powder was pulverized using a wet bead mill to adjust the particle size. It should be noted that the average particle size was adjusted by changing the pulverization time. The powders with adjusted particle sizes were wet mixed using a bead mill and dried.

[0120] [Average particle size]

[0121] The median diameter (D50) was determined as the average particle size of the particles from the volume-based particle size distribution using a laser diffraction / scattering particle size distribution analyzer (MT-3300 manufactured by Microtrac BEL).

[0122] [Volume expansion rate]

[0123] Acetylene black (conductive aid) and polyimide (binder) were mixed at a ratio of 80:5:15 (mass ratio) for particles with a particle size of about 15 μm to prepare a slurry. The slurry was applied to a stainless steel (SUS316L) foil with a thickness of 50 μm and dried to obtain a working electrode.

[0124] Next, a half-cell was prepared in which the counter electrode was a Li foil and a non-aqueous electrolyte was used. The non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1 mol / L in a mixed solvent of ethylene carbonate (EC) / dimethyl carbonate (DEC) = 1 / 1 (molar ratio).

[0125] The obtained half-cell was charged at a constant current of 0.1 mA until the voltage reached 0.002 Vvs. [Li + / Li]. Then, a micrometer is used to measure the change in thickness of the working electrode after charging relative to the thickness of the working electrode before charging. The value obtained by dividing the change in electrode thickness by the thickness of the electrode layer before charging and discharging is set as the volume expansion rate. The volume expansion rate of the particles after charging is calculated. The results are shown in Table 1. It should be noted that, although not shown in Table 1, the volume expansion rate of Si particles is 380%.

[0126] [Oxygen content]

[0127] The oxygen content of the second particle, particle B, was determined by the infrared absorption method of heating and melting in an inert gas (TC600 oxygen and nitrogen simultaneous analyzer manufactured by LECO Japan).

[0128] [Electrode capacity, cycle characteristics]

[0129] The obtained negative electrode active material 100 parts by mass, Ketjen black (Lion Co., Ltd.) 6 parts by mass as a conductive aid, and a thermoplastic resin, i.e., polyimide 19 parts by mass as a binder are mixed, and the mixture is dissolved or dispersed in N-methyl-2-pyrrolidone (NMP) as a solvent to obtain a paste. The obtained paste is applied to the surface of a stainless steel (SUS316L, thickness 20 μm) foil using a doctor blade method with a thickness of 50 μm. Next, it is dried and the negative electrode active material layer is compacted by rolling. Next, it is punched into a disc with a diameter of 11 mm and used as a working pole.

[0130] The working electrode obtained above was arranged on the positive electrode can of the button-type single cell, and a Li foil (thickness 500 μm) with a diameter of 11 mm was arranged on the negative electrode can as a counter electrode, and a polyolefin-based microporous membrane as a separator was arranged between them. Next, as an electrolyte, a non-aqueous electrolyte solution in which LiPF6 was dissolved at a concentration of 1 mol / L was injected into a mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 1 / 1 (molar ratio), and the positive electrode can and the negative electrode can were riveted and fixed, thereby making a button-type battery as a half-cell.

[0131] A button-type battery was used to perform one cycle of constant current charge and discharge at a current value of 0.2 mA. The initial discharge capacity C0 (mAh / g) was calculated from the value obtained by dividing the capacity (mAh) used during Li release by the mass (g) of the negative electrode active material.

[0132] The results are shown in "Electrode Capacity (Initial)" of Table 1. The evaluation criteria are as follows: ◎, ○, or △ indicates passing, and × indicates failing.

[0133] ◎: Initial discharge capacity is 2500mAh / g or more

[0134] ○: Initial discharge capacity is 1000mAh / g or more and less than 2500mAh / g

[0135] △: Initial discharge capacity is 500mAh / g or more and less than 1000mAh / g

[0136] ×: Initial discharge capacity is less than 500 mAh / g

[0137] After the second cycle of the charge and discharge test, the charge and discharge test was performed at a 1 / 5C rate, i.e., a rate of charging or discharging within 5 hours. 50 charge and discharge cycles were performed, and the capacity retention rate after 50 cycles was calculated based on the following formula to evaluate the cycle characteristics.

[0138] {Discharge capacity after 50 cycles / initial discharge capacity (discharge capacity at the first cycle)}×100(%)

[0139] The results are shown in "Cycle Characteristics" of Table 1. The evaluation criteria are as follows: ◎, ○, or △ indicates pass, and × indicates fail.

[0140] ◎: Capacity maintenance rate is more than 90%

[0141] ○: Capacity retention rate is 70% or more and less than 90%

[0142] △: Capacity maintenance rate is 50% or more and less than 70%

[0143] ×: Capacity retention rate is less than 50%

[0144] [Table 1]

[0145]

[0146]

[0147] Based on the above results, the negative electrode active material of this embodiment has both high electrode capacity and good cycle characteristics. This is also considered to be because the large expansion of Si particles during Li absorption is alleviated in the entire electrode by mixing the first particles and the second particles with different volume expansion rates.

[0148] On the other hand, it can be seen that the cycle characteristics of Comparative Example 4 without the first particle or Comparative Example 5 without the second particle are low, and the effect of the present invention cannot be obtained by using only one of the first particle and the second particle. This is because when only Si particles and first particles are contained as in Comparative Example 5, the expansion difference between the first particle and the Si particle is large, and the electrode collapses. In addition, it is also considered that this is because when only Si particles and second particles are contained as in Comparative Example 4, in addition to Si particles, the second particles also expand to a certain extent due to Li absorption, and as a result, the overall expansion amount of the electrode becomes larger, and the electrode still collapses.

[0149] Comparative Example 2 or Comparative Example 3, Comparative Example 6 are examples of containing two kinds of particles with different volume expansion coefficients in addition to Si particles. However, even if two kinds of first particles are contained (Comparative Example 3, Comparative Example 6) or two kinds of second particles are contained (Comparative Example 2), good cycle characteristics cannot be achieved if another second particle or first particle is not contained. This is because, as in Comparative Examples 4 and 5, when the expansion difference is above a certain level and different particles are not contained, the electrode collapses. In addition, in Comparative Example 6, AlNi is used as particle B, but the volume expansion coefficient of this AlNi is 240% in other embodiments or Comparative Example 2. In contrast, since the oxygen content of AlNi is as high as 5.2% by mass, its volume expansion coefficient is greatly reduced to 39%. As a result, it becomes a particle that does not meet the condition of the second particle, that is, the volume expansion coefficient caused by Li absorption does not meet 100 to 300%.

[0150] Comparative Example 1 is an example containing first particles and particles having a larger volume expansion rate than the second particles in addition to Si particles. As a result, it is found that good cycle characteristics cannot be achieved, and since the volume expansion rate of the second particles ranges from 100 to 300%, the effect of the present invention is exerted when used in combination with the first particles.

[0151] From the results of Examples 1 to 18, it was confirmed that the effects of the present invention can be widely obtained regardless of the types of particles by containing two types of particles having volume expansion coefficients within the range of the first particles and the second particles in addition to Si particles.

[0152] The results of Examples 2, 22 and 24 and the results of Examples 14, 21 and 23 show that the cycle characteristics are good when the average particle size of the Si particles and the second particles is 5 μm or less. This is also considered to be because the smaller the average particle size, the smaller the absolute amount of volume expansion.

[0153] According to the results of Examples 14, 19, 20, and 25 to 30, by making the content of Si particles above a certain level, a high electrode capacity is obtained. On the other hand, if the content of the first particles and the second particles is relatively reduced, the cycle characteristics are also reduced. Therefore, it is desirable to make the content of each particle appropriate according to the desired characteristics.

[0154] According to the results of Comparative Examples 3 or 5, good cycle characteristics cannot be obtained if the second particles are not contained, while the cycle characteristics are improved when only 1 mass % of the second particles are contained as in Example 25. Thus, it can be seen that the effect of the present invention is exerted even if the content of the second particles is less than that of the first particles.

[0155] The present invention is described in detail and also described with reference to specific embodiments. It is known to those skilled in the art that various changes or modifications can be made without departing from the spirit and scope of the present invention. This application is based on a patent application filed in Japan on July 29, 2022 (Japanese Patent Application No. 2022-122195) and a patent application filed in Japan on April 17, 2023 (Japanese Patent Application No. 2023-067211), the contents of which are incorporated herein by reference.

Claims

1. A negative electrode active material, characterized in that: Contains Si particles, first particles and second particles, The volume expansion rate of the first particle caused by Li absorption is 0 to 80%, The volume expansion rate of the second particles due to Li absorption is 100 to 300%.

2. The negative electrode active material according to claim 1, characterized in that The average particle size of the Si particles and the average particle size of the second particles are both 5 μm or less.

3. The negative electrode active material according to claim 1, characterized in that The content of the Si particles is 20 to 80% by mass, the content of the first particles is 10 to 70% by mass, and the content of the second particles is 1 to 60% by mass.

4. The negative electrode active material according to claim 3, characterized in that The content of the first particles is greater than the content of the second particles.

5. The negative electrode active material according to claim 1, characterized in that: The first particles are at least one particle selected from Fe, Al, Si and oxides thereof, and Ni, Ti, Cu, B, C, SiC and Si alloys.

6. The negative electrode active material according to claim 1, characterized in that The second particles are at least one particle selected from the group consisting of AlNi, AlTi, AlFe, and AlCu.

7. The negative electrode active material according to claim 6, characterized in that The second particles have an oxygen content of 4 mass % or less.

8. The negative electrode active material according to any one of claims 1 to 7, characterized in that The negative electrode active material is used in a lithium ion battery.

Citation Information

Patent Citations

  • Negative electrode active substance for lithium secondary battery, and method of manufacturing the same

    JP2012014866A

  • Vehicle structure

    JP2022122195A

  • Storage furniture

    JP2023067211A